The Critical Study of the Book of Ulum Al-Hadith (Muqaddimah) by Ibn Al-Salah - Dadah; Nur, Muh Arbiyansyah; Husaein, Muhammad (International Journal of Integrative Sciences, 2024)
The Muqaddimah by Ibn al-Salah serves as a foundational reference in the study of methodologies and principles within the science of hadith. This work addresses critical aspects related to the authenticity, validity, and methods of understanding hadith. Comprising 65 chapters, the Muqaddimah provides a comprehensive discussion of the disciplines of hadith science and has become an essential resource for scholars in the critique of hadith. This research was conducted to examine the characteristics of hadith classification found in the Muqaddimah of Ibn al-Salah. The research methodology employed in this study is qualitative descriptive, which elaborates on various topics to present a detailed and comprehensive understanding of the book’s content. The author references several works that discuss the Muqaddimah and the methodology employed by Ibn al-Salah in his classification of hadith. This includes consulting the primary source, the latest edition of the Muqaddimah, to validate the opinions of scholars who have analyzed the book. The findings reveal that the Muqaddimah by Ibn al-Salah is distinctive in its presentation. Unlike many subsequent works, it is not structured into chapters or sections, nor does it classify the topics systematically. Such a format was unconventional in many writings produced after the era of Ibn al-Salah.